Academic Misconduct within Higher Education in Canada - Hughes, Julia M. Christensen; McCabe, Donald L. (Canadian Journal of Higher Education, 2006)
Despite a plethora of research on the academic misconduct carried out by U.S. high school and undergraduate university students, little research has been done on the academic misconduct of Canadian students. This paper addresses this shortcoming by presenting the results of a study conducted at 11 Canadian higher education institutions between January 2002 and March 2003. We maintain that academic misconduct does indeed occur in Canada – amongst high school, undergraduate and graduate students. Common self-reported behaviours were as follows: working on an assignment with others when asked for individual work, getting questions and answers from someone who has already taken a test, copying a few sentences of material without footnoting, fabricating or falsifying lab data, and receiving unauthorized help on an assignment. Possible factors associated with these behaviours include student maturity, perceptions of what constitutes academic misconduct, faculty assessment and invigilation practices, low perceived risk, ineffective and poorly understood policies and procedures, and a lack of education on academic misconduct. Canadian educational institutions are encouraged to address these issues, beginning with a recommitment to academic integrity.